Generation of 3D ellipsoidal laser beams by means of a profiled volume chirped Bragg grating. (7th April 2016) - Mironov, S Yu; Poteomkin, A K; Gacheva, E I; Andrianov, A V; Zelenogorskii, V V; Vasiliev, R; Smirnov, V; Krasilnikov, M; Stephan, F; Khazanov, E A
Abstract: A method for shaping photocathode laser driver pulses into 3D ellipsoidal form has been proposed and implemented. The key idea of the method is to use a chirped Bragg grating recorded within the ellipsoid volume and absent outside it. If a beam with a constant (within the grating reflection band) spectral density and uniform (within the grating aperture) cross-section is incident on such a grating, the reflected beam will be a 3D ellipsoid in space and time. 3D ellipsoidal beams were obtained in experiment for the first time. It is expected that such laser beams will allow the electron bunch emittance to be reduced when applied at R ± photo injectors.